Hubungan Antara Self-Efficacy Akademik dan Konsep Diri Akademik dengan Prestasi Akademik - Chairiyati, Lisa Ratriana (Bina Nusantara University, 2013)
This study discusses the relationship between academic self-efficacy and academic self-concept with academic achievement. The design of the study was descriptive - correlational, with a study sample of 192 children. Statistical Analysis with SPSS computer method (Statistical Package for Social Science) version 17.0 for windows is used to find out characteristics of the respondents, and the regression analysis between the two independent variables (self-efficacy and academic self-concept academic) and the dependent variable (academic achievement) produce models regression . The results showed only variable Self-Efficacy (SE) contributes positively to academic achievement. It is supported by the value of t-statistic greater than 1, 645 for the value . Hence it can be said that the dependent variable (academic achievement) can be predicted with self-efficacy academic.